Fungsi Media Lembaga Penyiaran Publik (LPP) Radio Republik Indonesia (RRI) Padang Dalam Mengedukasi Masyarakat - Gabriella Afriza Ayu; Septria Andika; Rizki Syafril (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Public Broadcasting Institution (LPP) Radio Republik Indonesia (RRI) is one of the oldest broadcasting institutions in Indonesia which functions as national radio media. Radio Republik Indonesia (RRI) has a central role in providing information, entertainment for the community and education for the community. In the process of social communication, the ideal role of radio as a public medium is to accommodate as many needs and interests of its listeners as possible. Radio media has a very important role in providing education to the public. This article aims to determine the function of the Radio Republik Indonesia (RRI) Padang Public Delivery Institution (LPP) media in educating the public. This research uses an interview method with several sources. The results of this research explain the function of the Radio Republik Indonesia (RRI) Padang Public Delivery Institute (LPP) media in educating the public.